EARLY PROTEROZOIC CENTRAL-TYPE VOLCANO IN THE PECHENGA STRUCTURE AND ITS RELATION TO THE ORE-BEARING GABBRO-WEHRLITE COMPLEX OF THE KOLA PENINSULA - Skuf'in P.K.; Bayanova T.B. (My University, 2006)
The Zapolyarnyi volcanic center is confined to the boundary between the oldest volcanic formations (I and II) of the Pechenga complex. Its structure and rock association are significantly different from those of numerous eruptive centers of areal basaltic volcanism in the Pechenga structure. It is an oval-shaped body, 700 × 300 m in size, composed of volcanic eruptive lava breccia. The clastic material of the breccia includes angular and partially molten fragments of granites, pegmatoid granites, epidosites, quartz, and feldspars embedded in basaltic lava. The basalts are titanium-rich and iron-rich varieties enriched in large-ion lithophile elements (Rb, Ba, and Sr); they are similar in composition, including Rb-Sr and Sm-Nd isotopic characteristics, to the ferropicrites of the youngest volcanic formation (IV) and their differentiation products. The basalts of the volcanic center show εNd(T) values from -3.13 to -1.17. In general, these rocks definitely represent the vent facies of an Early Proterozoic central-type volcano. The age of the basalt of the volcanic center is 1918 ± 3 Ma (U-Pb method on zircon) and is similar to the previously determined age of volcanics of volcanic formation IV (1990 ± 40 Ma, Sm-Nd method). The rocks of this formation participated 2000-1900 Ma ago in the formation of the volcanoplutonic ore-bearing ferropicrite-gabbro-wehrlite association of the Pechenga structure. The age of the ore-bearing Pilguyarvi gabbro-wehrlite intrusion was constrained between 1987 ± 5 Ma (U-Pb method on zircon) and 1980 ± 10 Ma (U-Pb method on baddeleyite). In addition, the first data were obtained for the age of comagmatic olivine norites of the Nyasyucka dike complex in the northeastern flank of the Pechenga structure (1941 ± 3 Ma, U-Pb method on baddeleyite) and the peridotites of the Allarechka ore field in the southern framing of the Pechenga structure (1918 ± 29 Ma, U-Pb method on zircon), which were previously considered Archean. Taking into account the geological and geochemical characteristics of the rocks of the Zapolyarnyi paleovolcano and the identical age of the Ludikovian intrusions, it can be concluded that the basalts of the paleovolcano were formed during late stages of the evolution of Early Proterozoic basic-ultrabasic magmatism, which was characterized by extensive explosive activity and strong magmatic differentiation responsible for the generation of the ore-bearing intrusions of the ferropicrite-gabbro-wehrlite association. © Nauka/Interperiodica 2006.
Keywords: Proterozoic; Archean; Archean; Precambrian::Proterozoic; Докембрий::Протерозой; Precambrian::Archean; Докембрий::Архей; Precambrian::Archean